Creating a Sincere Sustainable Brand: The Application of Aristotle’s Rhetorical Theory to Green Brand Storytelling - Huang, Chaohua; Zhuang, Shaoshuang; Li, Ziyuan; Gao, Jingke (Frontiers in Psychology, 2022)
As consumers become skeptical of green products, green brands may need to put trust building on their business agenda. The study aims to use the rhetorical theory of Aristotle to examine the influence of a green brand story on perceived brand sincerity and brand trust. The study explores whether customer perceived value (CPV) mediates the effect between three means of persuasion used by a green brand story and perceived brand sincerity, and whether need for cognition (NFC) plays a moderating role. A model is proposed and tested through three independent experiments in which participants were exposed to green brand stories and asked to complete a questionnaire. Results show that the green brand story with three means of persuasion has a more positive impact on perceived brand sincerity and brand trust than the green brand story without, and the impact is partially mediated by CPV. Besides, NFC moderates the effect: perceived brand sincerity of green brands improves with three means of persuasion-laden story when NFC is relatively high. Specifically, the study reveals that pathos and ethos in a green brand story have positive effects on perceived brand sincerity through emotional value and social value, but the effect of logos is not identified. The findings contribute to the literature of brand storytelling, brand personality and green marketing, and have managerial implications for green brands to sustain customer-brand relationship.